Sosialisasi BUD untuk Mencegah Kesalahan dalam Penggunaan Obat di Lapangan Stadion Teladan Medan - Muharni Saputri; Nilsya Febrika Zebua; Sudewi Sudewi; Supran Hidayat; Dea Anggraini; Nurul Karima; Shadiq Suwailim; Hafizurrahman Hafizurrahman (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2023)
The success of treatment is determined by various aspects, starting from the right dose, the right route, the right medicine, knowing the right medicine, good packaging and understanding about BUD (Beyond Use Date). There are still many people who cannot distinguish between ED (Expire Date) and BUD. So far, ordinary people generally only recognize ED compared to BUD. This was shown in the question and answer activity in one group who thought that BUD was the same as ED. One of the men in the group explained that cough medicine is stored in the refrigerator and used for months as long as the medicine is still available and can be given to other patients. BUD is a very important aspect as it relates to drug stability and quality. BUD is a limitation on the use of drugs or the use of drugs after the primary packaging is opened or tampered with. The method used in this community service activity is to explore information to the community, to what extent they know the BUD on all forms of drug preparations, then from extracting this information, the team in community service activities provides explanations to the community around the Teladan Medan Stadium field on June 18, 2023, totaling 25 people with age variations ranging from 20 - 50 years. The results of this community service activity showed an increase in community understanding which was marked by the community's ability to answer questions.